(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The state and provision level of road traffic participants to the objects of service on Egypt highways have been analysed. In general, there are a number of significant shortcomings regarding the systematic approach in justifying and standardizing the distances of the road services location, considering the requirements of road users. With the help of Google Earth and real survey, the current status of the service objects along the Egypt highways and in foreign countries of the world has been surveyed. The obtained data show that service facilities are unevenly located in Egypt, often do not meet normative requirements and are not characterized by complexity. Instead, in foreign countries there is even more distribution of complex service facilities along highways, all service facilities has transition-high-speed bands and the vast majority have separate congresses.